Encapsulation of miRNA and siRNA into Nanomaterials for Cancer Therapeutics - Mina Zare; Rakesh Pemmada; Maya Madhavan; Aswathy Shailaja; Seeram Ramakrishna; Sumodan Padikkala Kandiyil; James M. Donahue; Vinoy Thomas (MDPI AG, 2022)
Globally, cancer is amongst the most deadly diseases due to the low efficiency of the conventional and obsolete chemotherapeutic methodologies and their many downsides. The poor aqueous solubility of most anticancer medications and their low biocompatibility make them ineligible candidates for the design of delivery systems. A significant drawback associated with chemotherapy is that there are no advanced solutions to multidrug resistance, which poses a major obstacle in cancer management. Since RNA interference (RNAi) can repress the expression of genes, it is viewed as a novel tool for advanced drug delivery. this is being explored as a promising drug targeting strategy for the treatment of multiple diseases, including cancer. However, there are many obstructions that hinder the clinical uses of siRNA drugs due to their low permeation into cells, off-target impacts, and possible unwanted immune responses under physiological circumstances. Thus, in this article, we review the design measures for siRNA conveyance frameworks and potential siRNA and miRNA drug delivery systems for malignant growth treatment, including the use of liposomes, dendrimers, and micelle-based nanovectors and functional polymer-drug delivery systems. This article sums up the advancements and challenges in the use of nanocarriers for siRNA delivery and remarkably centers around the most critical modification strategies for nanocarriers to build multifunctional siRNA and miRNA delivery vectors. In short, we hope this review will throw light on the dark areas of RNA interference, which will further open novel research arenas in the development of RNAi drugs for cancer.